(untitled) (Journal of the College of Basic Education, 2025)
Aesthetic taste plays a role in refining the recipient’s senses, forming his personality, and raising his level of sense of beauty, and his interaction with things, shapes, and colors in his surrounding environment. Developing the student’s aesthetic taste has a positive impact on the general aesthetic taste of society. Therefore, the researcher proposed the seven-cycle learning strategy to develop aesthetic taste among students, as it is one of the modern strategies in teaching. Based on its positive impact in developing mental abilities and providing students with educational skills and experiences, this has been proven by a number of studies. Based on the above, the researcher formulated his research problem: (Is it possible to develop aesthetic taste among middle school students using the 7E’s learning cycle strategy?), and the research aimed to (measure the effect of using the 7E’s learning cycle strategy in developing aesthetic taste among middle school students). The researcher also formulated the research hypothesis (There are no statistically significant differences at the level (0.5) between the average scores of the experimental group students before and after the aesthetic taste test), and the community consisted of The research was conducted on fifth-grade students in the scientific branch of the Baghdad Karkh Education Directorate, the first morning study. The researcher chose (30) students from among them to represent the research sample. The researcher built an achievement test for aesthetic taste and used the Wilcoxon rank sign test to reach the results. He concluded that using the 7E’s learning cycle strategy had a positive effect in raising the level of aesthetic taste among middle school students. The researcher recommended that art education teachers use the 7E’s learning cycle strategy in teaching students because of its positive effect on their learning and developing their aesthetic skills and experiences.